2004
DOI: 10.2519/jospt.2004.34.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Electrical Stimulation for Quadriceps Muscle Strengthening After Bilateral Total Knee Arthroplasty: A Case Series

Abstract: Study Design: A case series. Objectives: The purpose of this case series was to assess the effect of high-intensity neuromuscular electrical stimulation (NMES) on quadriceps strength and voluntary activation following total knee arthroplasty (TKA). Background: Following TKA, patients exhibit long-term weakness of the quadriceps and diminished functional capacity compared to age-matched healthy controls. The pain and swelling that results from surgery may contribute to quadriceps weakness. The use of high-inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 40 publications
1
96
0
10
Order By: Relevance
“…Although the mechanisms mediating the improvement in muscle function parameters induced by NMES training have not been fully elucidated, researchers have mainly documented the occurrence of neural adaptations. For example, surface electromyographic (EMG) activity and activation of the plantar Xexor (MaYuletti et al 2002a) and knee extensor (Stevens et al 2004;Gondin et al 2005) muscles have been shown to increase signiWcantly after multiple sessions of NMES. In the same way, signiWcant cross-education eVect (Hortobagyi et al 1999), acute facilitative eVects (Howard and Enoka 1991) and observations on the speciWcity of NMES training eVects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms mediating the improvement in muscle function parameters induced by NMES training have not been fully elucidated, researchers have mainly documented the occurrence of neural adaptations. For example, surface electromyographic (EMG) activity and activation of the plantar Xexor (MaYuletti et al 2002a) and knee extensor (Stevens et al 2004;Gondin et al 2005) muscles have been shown to increase signiWcantly after multiple sessions of NMES. In the same way, signiWcant cross-education eVect (Hortobagyi et al 1999), acute facilitative eVects (Howard and Enoka 1991) and observations on the speciWcity of NMES training eVects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous muscle electrical stimulation (ES) has gained an important role in rehabilitation and physical therapy as an adjunct tool for restoration of muscle functionality (Snyder-Mackler et al 1994;Stevens et al 2004), treatment of patello-femoral pain syndrome (Callaghan and Oldham 2004) or strengthening of limb muscles in elderly subjects with joint osteoarthritis (Talbot et al 2003) and may find a clear application in all those conditions that require the selective training of a specific muscle, such as vastus medialis during the treatment of patellar malalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that lower burst duty cycles (10%-20%) are optimal for generation of maximum electrically induced torque in the biceps brachii, 4 finger flexors, 35 and wrist extensors 55 and produce less discomfort. 35,55 Despite the common use of NMES in clinical practice to increase the strength of knee extensor musculature, 6,29,38,[45][46][47]50 only 2 studies in the literature have assessed the effect of burst-duty-cycle duration on torque production of the quadriceps in healthy, untrained individuals. 33,37 The first study 33 compared 5 burst-duty-cycle durations (10%, 30%, 50%, 70%, and 90%) and found that a burst duty cycle of 10% elicited the strongest muscle contraction.…”
Section: T T Conclusionmentioning
confidence: 99%
“…28,30 To minimize fatigue, a 5-minute interval was provided between each repetition. 43,45 Verbal encouragement was given by the investigator for each trial. The average of the peak torque values obtained for the 3 trials was calculated and used for subsequent analysis.…”
Section: Maximum Voluntary Isometric Contractionmentioning
confidence: 99%
See 1 more Smart Citation